IMPROVING TEACHERSÃ¢â¬â¢ PROFESSIONALISM THROUGH MATERIALS DEVELOPMENT, INFORMATION TECHNOLOGY AND CLASSROOM ACTION RESEARCH - Emalia Iragiliati Sukarni (TEFLIN, 2009)
Abstract: One of the ways to promote the International standard schoolsÃ¢â¬â¢ teacher professionalism was to carry out weekly workshops on material development based on curriculum pathways of the National Plus High Schools using the Information Technology (IT) facilities. This research developed teacher-made materials for the X grade. The materials were graded: narrative, recount, news item, descriptive, ranging from 250 to 500 words. The materials were then tried out in a Classroom Action Research (CAR) at eight classes of X grades. Based on previous research, teachersÃ¢â¬â¢ preferences are made in line with the studentsÃ¢â¬â¢ choice of issues to be discussed. It aimed at knowing the feasibility of the materials, the studentsÃ¢â¬â¢ preference of exercises and studentsÃ¢â¬â¢ level of competencies of each class related to the understanding of the units. Results of the questionnaires showed that most of the materials were understood and liked by the students. Thus, professionalism was seen during the process of the CAR.